Effectiveness of an education program for Caregivers Knowledge Related to Management of Children with Growth Hormone Deficiency in Outpatient Endocrine Clinics - abbas, Fatima; Ma`ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: The study aims to assess and evaluate the caregivers  knowledge  about management of the children with growth hormone deficiency and to find out the relationship between caregivers kowledge and caregivers age, gender, number of individual in house hold, Date of treatment started ,Caregivers level education and economic status Methodology: Quazi expermental study design was carried out at (Child's Central Teaching Hospital, Medical City of Al Imamian Al Khadhmain Teaching Hospital, and National Centre for Treatment and Research of Diabetes,Specialized Center for Endocrine Diseases and Diabetes, and Department of Medical City Children Welfare Teaching Hospital started  from  novomber 6th , 2017 through july   1st , 2018 , accidental (non-probability) sample of (80) caregivers  who were   attending to outpatient endocrine clinics and centers.The data were collected through the use of constructed  questionnaire , which consist of two parts (1) demographic characteristic  (6 )items (2) caregivers  knowledge  which consist from 3 sections of (33 ) items .Validity of  the study was determined through the panel of (16) experts and the reliability of the study questionnaire through the pilot study.Descriptive statistical and inferential analysis by using spss , version 23Results: The findings of the study indicated that there is  statistical significant difference between caregivers knowledge and their demographic characteristic except gender, level of education ,and economic status.The study recommended that: necessary for early detection of growth hormone deficiency for children, providing special nurse in endocrine clinics and center to give high quality care for children and education for children and their caregivers about signs and symptoms of growth hormone deficiency